ranaazad wrote:
A4G wrote:
What is the value of h ?
(1) h^2 = 36
(2) h^2 + 12h = -36
From statement 2,
(h+6)^2 = 0
h+6 = 0
h = -6, that is clearly sufficient. In this case, B is sufficient
But l approached the statement differently,
h (h+12) = -36
Hence, h=-36 or h = -48. Two values for h. Hence insufficient. In this case the answer would be E
l know it's a silly mistake.
Could someone please clarify.
Regards,
Rana Azad
Hi Rana,
h (h+12) = -36 does not mean h =-36 or h=-48..
substitute and check..
h=-36......
h(h+12) = -36
so -36(-36+12) = -36.......... -36+12 = 1.. NO
h (h+12) = -36 does not mean h =-36
IT means the product of h and h+12 is -36...
so if h=-6, h+12 = -6+12 = 6...
and h*(h+12) = -6 * 6 = -36 ... correct..
Always take all to ONE side and solve
l understand now. Thank you very much, sir!
Heading towards perfection>>